The long-term mortality of spontaneous bacterial peritonitis in cirrhotic patients: A 3-year nationwide cohort study - Hung, Tsung-Hsing; Tsai, Chen-Chi; Hsieh, Yu-Hsi; Tsai, Chih-Chun (Turkish Journal of Gastroenterology, 2015)
Abstract Background/Aims: There is no nationwide population-based study for the long-term mortality after single episode of spontaneous bacterial peritonitis (SBP) in cirrhotic patients. Our study showed the short-term and long-term mortalities, and identified the mortality risk of SBP. Materials and Methods: The National Health Insurance Database, derived from the Taiwan National Health Insurance program, was used to collect data from 16,992 cirrhotic patients. These cirrhotic patients were classified into three groups: SBP group (n=451, 2.7%), ascites without SBP group (n=2,564, 15.1%), and non-ascites (n=13,977, 82.3%) group. Each patient was followed up to 3 years after the initial hospitalization. Results: The 30-day mortalities in SBP, ascites without SBP, and non-ascites groups were 24.2%, 14.1%, and 8.1%, respectively. The 3-year mortalities in SBP, ascites without SBP, and non-ascites groups were 66.5%, 61.1%, and 41.5%. After Cox’s regression analysis adjusted by the patients’ age, gender, and underlying medical disorders, the SBP patients (hazard ratio=2.52) and ascites without SBP patients (hazard ratio=1.91) have higher risk for 3-year mortality than those without ascites. Conclusion: Cirrhotic patients with SBP have a 2.5-fold increase of 3-year mortality, compared to those without ascites.